(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Technological advancements in computing and communication technology have most recently grown rapidly. This growth has further been motivated by the high-speed networks and the declining cost of purchasing computers. The trend has enabled the running and fast transfers of various applications such as data and information, graphics, voice and movies.Â The use of computers and technology in communication has transformed various organizational systems to the digital era.